Fibroid vascularisation assessed with three‐dimensional power Doppler ultrasound is a predictor for uterine fibroid growth: a prospective cohort study. (12th April 2017) - Nieuwenhuis, LL; Keizer, AL; Stoelinga, B; Twisk, JWR; Hehenkamp, WJK; Brölmann, HAM; Huirne, JAF
Abstract : Objective: To analyse fibroid vascularisation measured with three‐dimensional (3D) power Doppler in relation to absolute fibroid volume change during 12 months of follow up and in relation to fibroid growth rate per year. Design: A prospective cohort study was performed between March 2012 and March 2014. Setting: Outpatient clinic of the VU medical centre, Amsterdam. Population or sample: All premenopausal women diagnosed with a maximum of two fibroids with expectant management were consecutively included. Methods: Three‐dimensional ultrasound including power Doppler was performed at baseline, 3, 6 and 12 months. Volume and vascular parameters were calculated using VOCAL software. Main outcome measures: The relationship between vascular index (VI) at baseline and fibroid volume over time was analysed using linear mixed model analyses for repeated measurements. Second, the relationship between VI at baseline and fibroid growth rate per year was calculated using linear regression analyses. Analyses were adjusted for possible confounders. Results: In all, 66 women (mean age 42 years) completed 12 months of follow up without treatment. Baseline fibroid vascularisation (VI) measured with 3D power Doppler is correlated with fibroid volume at 12 months ( P = 0.02 ). An increase of 1% in VI at baseline was associated with a 7.00‐cm 3 larger fibroid volume at 12 months. Furthermore, vascularisation was also associated with fibroid growth rate per year ( P = 0.04). Conclusion: In women with uterine fibroids without therapy, baseline vascularisation (VI) measured with 3D power Doppler is correlated with absolute fibroid volume change at 12 months and with fibroid growth rate per year. Tweetable abstract: Fibroid vascularisation correlates with absolute fibroid volume change and fibroid growth rate per year. Tweetable abstract: Fibroid vascularisation correlates with absolute fibroid volume change and fibroid growth rate per year.